Islamic Religious Education Learning in a Multicultural Society: A Dialogical Approach, the Role of Teachers, and the Integration of Religious Moderation Values - Naila Rizqiyana; Luthfia Rosidin; Nuraini Irmasari; Nabilah Ulin Nimah; Himatun Nisa (al-Iltizam: Jurnal Pendidikan Agama Islam, 2026)
An education system capable of instilling the values ​​of moderation and tolerance is essential for Indonesia's culturally, ethnically, and religiously diverse society. The purpose of this study is to examine how Islamic Religious Education (PAI) is implemented in a multicultural society. This includes aspects such as learning methods, teacher roles, and challenges encountered. This study employed qualitative methods and literature review. Various relevant scientific sources on Islamic education and multiculturalism were analyzed. The results indicate that the curriculum must systematically integrate the values ​​of tasamuh (tolerance), ukhuwah (brotherhood), and wasathiyah (religious moderation). PAI learning must be developed through a dialogical, participatory, and contextual approach. PAI teachers play a crucial role as facilitators and role models in creating an inclusive learning environment that values ​​diversity. Furthermore, improving digital literacy and developing a multicultural-based curriculum are strategic steps to address discrimination, radicalism, and the challenges of globalization. The results of this study indicate that PAI learning designed in an inclusive and moderate manner significantly contributes to producing a generation that is faithful, tolerant, and able to live together in a diverse society.